Effect of substrate temperature on structure, magnetic and electrical transport properties of Mn1.60Ga films. (20th January 2020) - Zhang, Yumei; Yang, Chaoqun; Wang, Li; Bai, Yidan; Liu, Sitong; Li, Haibo
Abstract: L 10 -MnGa alloys have great application potential in the fields of permanent magnet and spintronics. L 10 -Mn1.60 Ga thin films were prepared on MgO (100) substrates by magnetron sputtering under different substrate temperatures ranging from 200 to 600 °C, and the effect of the substrate temperature on the structure, magnetic and electrical transport properties of the films were observed. The results show that the films deposited at 300–600 °C substrate have good (001) orientation. The coercivity and effective anisotropy of film are enhanced at 400 °C substrate temperature, because the large tensile stress/strain induces a large coercivity and high effective anisotropy. When the substrate temperature increases to 500 °C, and the abnormal Hall resistivity of the film reaches the maximum value. The magnetic and electrical transport properties of the L 10 -Mn1.60 Ga film are improved effectively with an appropriate substrate temperature.